The Concept of Ḥiyāl in Marriage: A Preliminary Review - Ahmad Syakir Mohd Nassuruddin; Mohd Zain Mubarak; Zulfaqar Mamat; A’inaa Lyana Amanina Mohd Zaim (Rabbanica: Journal of Revealed Knowledge)
Ḥiyāl is the ability to find a way out of a legal problem using certain methods. Ḥiyāl occurs either in worship, muamalat, or crime, including marriage. Ḥiyāl in this marriage is more focused on the issues prescribed by the Sharia even though scholars differ in their application. However, the scope of practising ḥiyāl in today's marriages is growing and requires in-depth analysis. Therefore, the objective of this study is to explain the concept of ḥiyāl in marriage based on the views of the majority of scholars. In the meantime, the study also identifies the form of ḥiyāl in marriage and the application of law to it. The research uses a qualitative form through the library method. Data collection for this study draws from multiple sources, including classical Islamic jurisprudence texts, contemporary scholarly works, academic journal articles, theses, scholarly publications, and research reports. Thus, data was analysed using a content analysis approach through predetermined themes. The study results found that ḥiyāl in marriage is more likely not to fulfil the maqāsid and purpose in marriage. This is because some of the definitions of ḥiyāl can lead to negative connotations, but some scholars require the use of ḥiyāl as long as it does not conflict with the maqasid of syarak. Ḥiyāl in marriage is divided into five forms, namely Nikah Taḥlīl, Nikah Mut'ah, Nikah Syighār, Nikah Misyār and Nikah Sirri. The determination of the law for these five forms of ḥiyāl is subject to maslahah to ensure harmony and integrity of the household can be achieved.